A DNA break-5mC cycle activates transposable elements in Arabidopsis - Wenjie Liang; Haokai Cao; Chen Zou; Xindong Tong; Yongbo Ma; Yitong Shen; Xue Han; Yilin Zhang; Binglian Zheng; Jinchao Li (Proceedings of the National Academy of Sciences, 2026)
Plant genomic and epigenomic integrity are perpetually threatened by exogenous and endogenous DNA damage. However, the interplay between DNA damage, DNA methylation (5mC), and transposable element (TE) activity remains poorly understood. Here, we demonstrate that defective single-strand break (SSB) repair acts as a potent trigger for genome-wide TE derepression and extensive de novo DNA methylation in Arabidopsis . Mutations in ZDP/APE2, which encode conserved DNA 3’-end repair enzymes, impair the repair of 3’-blocked SSBs arising from base excision repair, ultimately leading to widespread TE activation. Concurrently, inefficient SSB repair activates the ATR–SOG1-mediated DNA damage response, which enhances the RNA-directed DNA methylation (RdDM) pathway to counteract TE activation by depositing 5mC. Paradoxically, the resulting methylation is excised by the DNA demethylase ROS1—a process that itself generates 3’-blocked SSBs requiring resolution by ZDP/APE2. In zdp ape2 mutants, ROS1-mediated 5mC excision produces additional SSBs, which in turn reactivate RdDM. This establishes a self-sustaining SSB–5mC cycle that perpetuates DNA damage and drives massive TE activation in the mutant. Our findings reveal a critical mechanistic link between SSB repair, DNA methylation dynamics, and TE derepression, positioning defective SSB repair as a major inducer of epigenomic instability.